The Role of Law in Indonesia's Economic Development in the Digital Era - Sinaga, Wetmen (Advances in Social Sciences Research Journal, 2023)
The current digital economy raises demands from business people to carry out activities online. Law No. 5 of 1999 about the Prohibition of Monopolistic Practices and Unfair Business Competition, is still unable to accommodate the impact of the digital economy that will emerge in the future. The development of the digital economy will lead to an increase in the ability of digital platforms to collect more data, increase the competitiveness of online store owners and with the emergence of several applications, so that the dominant position of digital platforms can be misused which can result in competitors being uncompetitive at the market level. Related to this, it is necessary to have regulations that regulate in a more detailed scope related to the existence of juridical protection of personal data of people which in the future will be required in data collection on the ongoing practice of changing digital economy.